Public Health Impact of Potential Infant MenACWY Vaccination Strategies in Spain - Katharina Schley; Jamie Findlow; Carlos Molina; Shannon M. Sullivan; Eszter Tichy (Vaccines)
Background: The Spanish Interterritorial Council of the National Health System (a central government body) currently recommends vaccination against meningococcal serogroup C (MenC) at 4 and 12 months of age for prevention of invasive meningococcal disease (IMD). The Advisory Committee on Vaccines of the Spanish Association of Pediatrics (a professional medical association) and numerous Spanish regional bodies instead recommend quadrivalent vaccination against serogroups A, C, W, and Y (MenACWY) at 4 and 12 months of age. The central government and Spanish Association of Pediatrics also recommend MenACWY vaccination at 12 years of age. This study assessed the potential public health effects of replacing the MenC vaccination schedule with different MenACWY vaccination schedules in infants. Methods: Here, a static multi-cohort population model was used to evaluate potential effects on public health of IMD due to meningococcal serogroups C/W/Y, comparing MenC infant vaccination (reference strategy) against four different strategies including quadrivalent tetanus toxoid conjugate vaccine (MenACWY-TT; Nimenrix®, Pfizer Europe MA EEIG, Brussels, Belgium) infant vaccination; all strategies included MenACWY-TT vaccination at 12 years of age. Results: The most effective strategy for infant vaccination was MenACWY-TT at 2, 4, and 12 months, preventing an estimated additional 103 IMD cases, 17 deaths, and 41 cases with long-term sequelae (LTS) versus the reference strategy in the base-case IMD incidence scenario. When strategies included a two-dose infant schedule, the earlier the infant MenACWY-TT vaccine was administered, the more additional cases, deaths, and cases with LTS were prevented (base-case and high-incidence scenarios). Conclusions: This analysis supports implementation of MenACWY-TT as a replacement for MenC vaccination.